Omnibus interior lighting system using LEDs and automotive communication network - Cervi,Murilo (2006)
This paper presents an intelligent lighting system for bus interior environment using LEDs (Light Emitting Diodes) controlled through an automotive communication network. The system consists of a master central control and slave lighting modules, using a LIN protocol (Local Interconnect Network) to perform communication. This network is a low cost alternative to the proposed system requirements, due to its low bit rate and physical needs. Each slave is an independent lighting module that supplies a group of LEDs and measures the environment lighting level. The master sets LEDs module parameters (slaves), such as the state (on/off) and desired lighting level. Besides, the master makes the user interface and establishes communication with other bus systems through a CAN (Controller Area Network) gateway. This paper presents a complete logical description, including block and state diagrams, a physical description and some relevant experimental results of the proposed system.